2016
DOI: 10.1155/2016/8530574
|View full text |Cite
|
Sign up to set email alerts
|

Load Bearing and Deformation Characteristics of Granular Spoils under Unconfined Compressive Loading for Coal Mine Backfill

Abstract: The load bearing capacity and deformation response of granular spoils under uniaxial compression are numerically and experimentally investigated, aiming to shed light on the performance of back filled waste spoils while controlling ground subsidence after coal extraction. In numerical study, the particles are assembled in PFC commercial code in light of the digitized real shape of spoils with image technique, which is proved to be consistent with the physical test. The results from numerical and laboratory exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…More complicated mining conditions and dynamic processes, such as jointed overburden strata [70], multi-seam mining [71], and domino-like collapse disaster of room-and-pillar mines [72], can also be investigated. Numerical simulation methods have been an important tool in mine design and mine behavior analysis [73][74][75][76][77][78].…”
Section: Numerical Simulation Methodsmentioning
confidence: 99%
“…More complicated mining conditions and dynamic processes, such as jointed overburden strata [70], multi-seam mining [71], and domino-like collapse disaster of room-and-pillar mines [72], can also be investigated. Numerical simulation methods have been an important tool in mine design and mine behavior analysis [73][74][75][76][77][78].…”
Section: Numerical Simulation Methodsmentioning
confidence: 99%
“…In China, underground coal mines produce about 95% of total coal [1]. Underground coal mining indeed contributes a large amount of coal, but it also creates a tremendous amount of mined-out void and discharges a great deal of solid waste [2,3]. Most of the waste is coal gangue, and it is reported that approximately 4.5 billion tons of coal gangue is stocked in China at present [4].…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al [26] investigated the relationship between the compression ratio, lateral pressure, and particle gradation of waste-rock samples in a systematic series of compression tests. Li et al [27] applied numerical simulation experiments to study the loading capacity and deformation response of filling particles under uniaxial compression. Ma et al [28] indicate that the effective porosity of crushed limestone samples decreases with the decrease in bigger particle size.…”
Section: Introductionmentioning
confidence: 99%